Can Platforms Affect the Safety and Efficacy of Drug-Eluting Stents in the Era of Biodegradable Polymers?: A Meta-Analysis of 34,850 Randomized Individuals. - Yun-Feng Yan (PLoS ONE, 2016)
OBJECTIVE:In the era of bare metal stents (BMSs), alloys have been considered to be better materials for stent design than stainless steel. In the era of biodegradable polymer drug-eluting stents (BP-DESs), the safety and efficacy of BP-DESs with different metal platforms (stainless steel or alloys) have not yet been reported, although their polymers are eventually absorbed, and only the metal platforms remain in the body. This study sought to determine the clinical safety and efficacy of BP-DESs with different platforms compared with other stents (other DESs and BMSs). METHODS:PubMed, Embase and Clinical Trials.gov were searched for randomized controlled trials (RCTs) that compared BP-DESs with other stents. After performing pooled analysis of BP-DESs and other stents, we performed a subgroup analysis using two classification methods: stent platform and follow-up time. The study characteristics, patient characteristics and clinical outcomes were abstracted. RESULTS:Forty RCTs (49 studies) comprising 34,850 patients were included. Biodegradable polymer stainless drug-eluting stents (BP-stainless DESs) were superior to the other stents [mainly stainless drug-eluting stents (DESs)] in terms of pooled definite/probable stent thrombosis (ST) (OR [95% CI] = 0.76[0.61-0.95], p = 0.02), long-term definite/probable ST (OR [95% CI] = 0.73[0.57-0.94], p = 0.01), very late definite/probable ST (OR [95% CI] = 0.56[0.33-0.93], p = 0.03) and long-term definite ST. BP-stainless DESs had lower rates of pooled, mid-term and long-term target vessel revascularization (TVR) and target lesion revascularization (TLR) than the other stainless DESs and BMSs. Furthermore, BP-stainless DESs were associated with lower rates of long-term death than other stainless DESs and lower rates of mid-term myocardial infarction than BMSs. However, only the mid-term and long-term TVR rates were superior in BP-alloy DESs compared with the other stents. CONCLUSION:Our results indirectly suggest that BP-stainless DESs may offer more benefits than BP-alloy DESs in the era of BP-DESs. Further well-designed RCTs comparing BP-stainless with BP-alloy DESs are needed to confirm which platform is better.